Fabrication of polyethersulfone membranes using nanocarbon as additive - Arahman, N. (GEOMATE International Society, 2018)
Membrane-based processes have become the most dominant technology for water or wastewater treatment. To maintain optimum performance, a membrane should have high permeability and selectivity, good hydrophilicity, in combination with stable mechanical properties. Generally, the membrane produced from pure polyethersulfone (PES) has good mechanical properties, but low hydrophilicity. Modifications of the PES membrane with hydrophilic additives can increase its hydrophilicity. Nevertheless, incorporating additives may decrease its mechanical properties. The objective of this study is to enhance the overall properties of PES membrane by incorporating nanocarbon as an additive. The goal is to obtain a membrane with high permeability and selectivity, good hydrophilicity, as well as superior mechanical properties. Four PES membranes were equipped via the dry-wet inversion method using two solvents (n-methyl-2-pyrrolidone (NMP) and dimethyl sulfoxide (DMSO)). The nanocarbon additive was fabricated from palm fruit-shell biomass wastes. The results show that the type of solvent affects the pore structure of the membrane surface. The membranes prepared using the PES-NMP system have dense structures with small nodules that appear in the upper skin layer, while the membranes from the PES-DMSO system have a spherulite-like structure. The membrane structures changed significantly when the nanocarbon particles were added to the polymer solution, particularly in terms of the shape and size of the microvoids. The finger-like structure found in the membranes prepared from PES-NMP or PES-DMSO systems disappears after the nanocarbon was added to the system. Furthermore, the accretion of nanocarbon to the polymer system increases the water permeability, hydrophilicity, and mechanical properties of the resulted membrane. Â© 2018, Int. J. of GEOMATE.